Association Between Vertebral Fracture and Diffuse Idiopathic Skeletal Hyperostosis. Issue 18 (15th September 2019) - Murakami, Yusuke; Mashima, Naohiko; Morino, Tadao; Fukuda, Takahiko; Iwase, Miho; Hino, Masayuki; Misaki, Hiroshi; Miura, Hiromasa
Abstract : Study Design: Retrospective case-control study. Objective: To investigate the prevalence and characteristics of diffuse idiopathic skeletal hyperostosis (DISH) in vertebral fracture patients admitted to our hospital. Summary of Background Data: Although vertebral fracture is generally treated conservatively with rest and use of a corset, surgery with rigid internal fixation is recommended for vertebral fractures in patients with DISH. Thus, treatment strategies for vertebral fracture differ according to the presence or absence of DISH. However, only a few studies have investigated the prevalence of DISH in vertebral fracture patients. Methods: A total of 159 patients (49 men and 110 women, with a mean age of 82.9 years) who were diagnosed with fresh vertebral fracture and required admission to HITO Hospital. The diagnosis of fresh vertebral fracture was made using x-ray imaging, computed tomography, and magnetic resonance imaging, and the presence or absence of DISH was assessed. In addition, age, sex, bone mineral density ( % young adult mean), blood test results, treatment, and length of hospital stay were compared between patients with and without DISH. Results: The proportion of patients with DISH among the patients with vertebral fracture was 33.9% (54 of 159 patients). The proportions in men and women were 38.8% and 31.8%, respectively, with no significant difference between sexes ( P = 0.39). The patients in the DISH group were older than those in the non-DISH group (83.6 vs. 79.4 years, P = 0.009), and the DISH group had higher glycated hemoglobin A1c ( P = 0.005), higher bone mineral density ( P = 0.042), and longer length of hospital stay ( P = 0.0001) compared with those in the non-DISH group. Conclusion: The proportion of patients with DISH among the vertebral fracture patients was 33.9%. Given that patients with DISH may require different treatment approaches, careful observation is needed. Level of Evidence: 3 Abstract : The proportion of patients with diffuse idiopathic skeletal hyperostosis (DISH) among the fresh vertebral fracture patients admitted to the HITO hospital was 33.9%, and DISH was associated with older age and higher glycated hemoglobin A1c and bone mineral density.